Chemical Composition of Essential Oil of Nepeta nuda L. subsp. nuda (Lamiaceae) from Turkey - Kilic, Omer; Hayta, Sukru; Bagci, Eyup (Chemical Publishing Co., 2011)
The chemical composition of the essential oil of dried aerial parts of Nepeta nuda L. subsp. nuda (Lamiaceae) from Turkey were analyzed by GC and GC-MS. The essential oil of Nepeta nuda subsp. nuda were obtained by hydrodistillation and 45 components representing 94.7 % of the total oil were identified. The main compounds of Nepeta nuda subsp. nuda were determined as camphor (23.5 %), 1,8 cineole (21 %), borneol (18.77 %) and camphene (6.50 %). The chemical distribution of the essential oil compounds in the genus pattern were discussed in means of chemotaxonomy and natural products.
Keywords: 1,8-Cineole; Camphor; Essential oil; Lamiaceae; Nepeta nuda L. subsp. nuda